(untitled) (Journal of the College of Basic Education, 2022)
This study deals with the magnitude of influence of various geographical factors and meteorological variables on land cover among six meteorological stations Rabiah, Anna, Kirkuk, Mosul, Baghdad and Najaf. The statistical analysis focuses on the means of annuals during 1961-1995 The geographical factors include distance from the Najaf station and the effect towards studied stations. The meteorological variables considered include wind speed, mean temperature and relative humidity. Regression analyses were performed with distance and surface temperatures. Results revealed that surface temperature affected land cover across all study. Temperatures in land cover (vegetated areas) were lower than those in other area in seasons. Relative humidity has significant on all the stations has been studied with land cover as getting increase as close to be near land cover, the relation stronger in the north and in winter season. Wind speed has no significant only minor influence in summer on the north stations,Rabiah,Anaa, Kirkuk and Mosul because the extension of the mountains from the northwest to the southeast is a responsible factor affecting the wind speed since, topographically ,lands are high in the west and east ,and depressed in middle and south. By calculating, adjusting and unified the studied station with same period for one high on sea level for mean temperature, it was found same result of effective of land cover. Introduction